2020
DOI: 10.1039/d0fo01496f
|View full text |Cite
|
Sign up to set email alerts
|

A chondroprotective effect of moracin on IL-1β-induced primary rat chondrocytes and an osteoarthritis rat model through Nrf2/HO-1 and NF-κB axes

Abstract: Osteoarthritis (OA) is a common joint disease characterized by cartilage degeneration and inflammation. Although moracin is known to play a role in anti-inflammation and anti-oxidation in several inflammatory diseases, its...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…The transcription factor NF-κB plays a critical role in the development of inflammation; it promotes the expression of inflammatory cytokines [ 21 ]. LPS-induced generation of pro-inflammatory mediators involves the NF-κB signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The transcription factor NF-κB plays a critical role in the development of inflammation; it promotes the expression of inflammatory cytokines [ 21 ]. LPS-induced generation of pro-inflammatory mediators involves the NF-κB signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…After stimulation, P65 is released from the cytoplasm into the nucleus when IκBα is phosphorylated and then degraded. P65 activates the transcription of inflammatory mediators in the nucleus [ 21 ]. Activated NF-κB, which is made up of p50 and p65, is phosphorylated and translocated to the nucleus, where it transcribes inflammation-related genes [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…# P < 0:05 vs. "sh-C" cells. 12 Oxidative Medicine and Cellular Longevity 13 Oxidative Medicine and Cellular Longevity OARSI scores than the DMM group. Furthermore, to investigate the effect of luteolin on ECM in vivo, immunohistochemical staining of Nrf2 and MMP13 in cartilage samples was carried out.…”
Section: Luteolin Ameliorated Oa Progression In the Dmmmentioning
confidence: 96%
“…After binding to antioxidant response elements (AREs) in gene promoters, Nrf2 promotes the transcription and expression of several antioxidant enzymes, such as hem oxygenase 1 (HO-1), NAD (P) H quinone oxidoreductase-1 (NQO1), and γ-glutamyl cysteine ligase catalytic subunit (GCLC) [10,11]. Furthermore, researches have revealed that Nrf2 boost protects chondrocytes against oxidative injury and inflammation, as well as attenuates OA progression in animal models [12,13].…”
Section: Introductionmentioning
confidence: 99%